The Antecedents And Consequences Of Work-Family Conflict Among Married Accountants In Penang - LEE HSIA, KHOR (2005)
The issue of work-family conflict among professionals has received a lot of attention in the academic field. The purpose of this research was to examine the antecedents (work-related factors and family-related factors) and consequences (job satisfaction, family satisfaction, and intention to turnover) of work-family conflict.